Analysis of Important Events in the Early Journey of Islam Through the Khaibar War and Wadi Al-Quran - Basri, Muhammad; Nasution, Rizka Hasanah; Darmawan, Anugrah Satria (Lembaga Riset Mutiara Akbar, 2024)
This research aims to investigate the strategic role of the Khaibar and Wadi Al-Qura wars in the spread of Islam in the early days of Islam. The research method used is literature study, with a focus on analyzing various aspects such as military, diplomacy, economics and culture. The main objective of the research is to understand how these wars influenced the strengthening of the military position of Muslims, handling ethnoreligious conflicts, strengthening the economy, expanding Muslim recruitment, the importance of diplomacy in agreements, and the continuation of Islamic da'wah. Literature studies were carried out by identifying, selecting and analyzing literary sources relevant to the Khaibar and Wadi Al-Qura wars. An in-depth analysis of the literature's content provides a holistic insight into the impact of these wars on the spread of Islam in the Arab region at that time. The research results show that the Khaibar and Wadi Al-Qura wars played an important role in strengthening the military position of Muslims, providing examples in handling ethnoreligious conflicts, strengthening the economy, expanding Muslim recruitment, and proving the importance of diplomacy in forming agreements that support the peaceful spread of Islam.